(untitled) (Journal of the College of Basic Education, 2023)
Political figures in the contemporary history of Iraq have received great attention from the scientific and academic circles, as these figures have become subjects of scientific studies in order to reveal the truth about their roles and influences in Iraqi political life, within the time frame of the historical actions of those figures, which contributes to the correct understanding of the movement of that movement. History and knowledge of the factors that influenced it, and its future directions, and among these intellectual and cultural personalities, who provided great services to study basic aspects of the contemporary history of Iraq, by writing down the events and developments of that history, and presenting its material to researchers preserved by important publications, from which they take a valid starting point for scientific studies in Their field of specialization, and standing at the forefront of those historians is Abd al-Zaraq al-Hassani, whose efforts have mainly focused, since 1929, and with his own diligence on codifying the history of Iraq during the royal era. Throughout more than (50) years spent in research and writing.